Epidemiological factors associated with immunological resistance in household contacts exposed to active tuberculosis in South Africa: A logistic regression analysis - Nomfanelo Maenetje; Matthew Oladimeji; Mandla Mlotshwa; Daniel Hoft; Christina Lindan; Robert Wallis; Salome Charalambous; Gavin Churchyard; Vinodh Edward; Andrew Fiore-Gartland; Jerry Shai; Pholo Maenetje (PLoS ONE, 2025)
Introduction Studying individuals who do not get infected with tuberculosis (TB) despite being persistently exposed to infectious TB may enable us to identify TB protective mechanisms. Methods Between Apr 2015 and Apr 2017, we recruited adult household contacts (HHCs) of index TB cases (GeneXpert and sputum smear-positive) in Rustenburg, South Africa. HIV-uninfected HHCs who tested positive on both Tuberculin Skin Test (TST) and QuantiFERON-TB Gold In-tube (QFT) were defined as having latent TB infection (QFT + TST+), and those who tested double negative (QFT-TST-) were defined as uninfected with TB. The level of risk for TB infection was evaluated using an epidemiologic risk score. We compared epidemiological and clinical characteristics between the groups and used logic regression to identify factors associated with being QFT-TST-. Results Of the 235 household contacts screened, 109 (46.3%) were QFT + TST + , 46 (19.5%) were TST-QFT-, 73 (30.1%) had discordant results, and 7 (2.9%) were excluded based on being HIV positive, already having active TB disease or had missing QFT/TST results. After 3 months, 27 (58.6%) of HHCs remained persistently negative. Younger age, higher number of household windows and habitable rooms, and relations with the index case were independently associated with being QFT-TST-. In the multivariable analysis, younger age (OR: 2.81, 95% CI, 1.23–6.47) and living in homes with more rooms (OR: 4.62, 95% CI, 1.81–11.79) remained associated with being QFT-TST-. We found no association between QFT-TST- and factors such as time spent with the index case, type of house, number of household occupants, or the risk score. Conclusion Our findings that both younger age and larger living quarters were associated with QFT-TST- status may suggest reduced exposure to TB. We found no association between the epidemiological TB risk score consisting of multiple TB infection risk factors and QFT-TST- status, suggesting other factors may play a role in remaining TB uninfected despite exposure.